Measurement of Vaccine Efficacy and Covid-19 Risk Probability - Defriman Djafri (Andalas University, Faculty of Public Health, 2022)
The effectiveness and efficacy of the Covid-19 vaccine are important indicators considered in implementing the vaccination program. This indicator is also a consideration for the community to receive the Covid-19 vaccine in the future. This calculation informs the community about the importance of the efficacy and effectiveness of the Covid-19 vaccination.